2017
DOI: 10.1021/acs.jnatprod.7b00554
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Cardiac Glycoside Constituents of Vallaris glabra Leaves

Abstract: Thirteen cardenolide glycosides (1-13) were isolated from the CHCl and MeOH extracts of Vallaris glabra leaves. The structures of the new compounds (2-13) were identified by spectroscopic methods, with the absolute configurations of the sugar moieties determined by acid hydrolysis. All compounds were evaluated for their cytotoxic activity against human cervix adenocarcinoma, lung carcinoma, and colorectal adenocarcinoma cell lines. The two most potent compounds [2'-O-acetylacoschimperoside P (1) and oleandrige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
(48 reference statements)
1
16
0
Order By: Relevance
“… 34,35 Furthermore, observation of two pairs of related compounds 5/6, and 7/8 indicated that cardiac glycosides displayed weaker cytotoxicities with an increase in the number of sugar units. The sugar moiety is another factor while determining cytotoxic activity, 34 but the sugar moieties were less active than C-10 groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 34,35 Furthermore, observation of two pairs of related compounds 5/6, and 7/8 indicated that cardiac glycosides displayed weaker cytotoxicities with an increase in the number of sugar units. The sugar moiety is another factor while determining cytotoxic activity, 34 but the sugar moieties were less active than C-10 groups.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, OH-5 and OCOCH 3 -16 were the potential cytotoxic groups compared with these compounds, and the results were supported by the results given in the literature. 34,35 Furthermore, observation of two pairs of related compounds 5/6, and 7/8 indicated that cardiac glycosides displayed weaker cytotoxicities with an increase in the number of sugar units. The sugar moiety is another factor while determining cytotoxic activity, 34 but the sugar moieties were less active than C-10 groups.…”
Section: Cytotoxic Activities Of Compoundsmentioning
confidence: 99%
“…With IC50 values ranging from 0.03-0.07 µM, it showed significant cytotoxic action against the HTB38 cell line. [78] Crude saponins from fruits…”
Section: Vallaris Glabramentioning
confidence: 99%
“…Partially hydrogenated N-heterocycles (azolines), in particular 2-oxazolines, 2-thiazolines, and 2-imidazolines, are important synthetic targets, not only due to their abundance in biologically active compounds, [1][2][3][4][5][6][7] but also due to their high value as useful synthetic building blocks. [8][9][10][11][12][13] Enantiopure derivatives substituted either at C4, at C5, or at both saturated carbons are of particular importance due to the stereochemical requirements of the desired products or the chiral building blocks made by them. Enantiopure 4-oxazolines are also widely applied as core structural motifs, for example in chiral ligands for enantioselective transition metal-catalyzed reactions.…”
mentioning
confidence: 99%
“…Decreasing the catalyst loading to 5 mol% had a negative effect on the yield. Reduction of the reaction time or performing the reaction at 0 °C did not improve the enantioselectivity but only led to lower reaction rates and incomplete conversions (See entries [12][13].…”
mentioning
confidence: 99%